Incentive of job stability and its relationship to the performance of the worker in the industrial establishment: The case of Sarmook Company for Oriental Drinks, Setif, Algeria - Benmansour, Rafika (Journal of Economic, Administrative and Legal Sciences, 2025)
Our research topic stems from organizational problems linked to the internal environment of organizations, especially  the stimulus of job stability and its relationship with functional performance in industrial organizations. Thus, we have to research job stability nature and how to reinforce it within the organizational pattern without its being other than a defensive mechanism used by employees to remain in the institution in light of the increase of the demand for preferred recruitment, and how the latter influences the efficiency of performance and increases its levels. Therefore, we put the variants of job stability and functional performance in their conceptual and theoretical contexts as an attempt to examine their relationship so that we can apply them to the organizational reality for the empirical methodological approach in order to strengthen the organizational structural vision. We used the descriptive analytical methodology with its characteristics that would enable us to obtain the data needed for conducting this study. To achieve it, we employed direct observation, questionnaire and interview. In addition, we ended with a sociological reading for the study results that included a reading for it in light of the assumptions and objectives of the study as well as the theoretical patrimony proved the existence of a substantial relationship between job stability and job performance. To consolidate this relationship, we included in this study a number of recommendations, among which the most important was the necessity to establish organizational justice in the subject organization to ensure the sought-after efficiency of the human resource.
Keywords: Functional performance; incentives; stimulus of job stability